The Effect of Beet Juice Intake on Increasing Hemoglobin Levels in Adolescent Girls with Anemia: A Literature Review - Handayani, Oktavia; Widhi Astuti, KH Endah; Puspita Sari, Lutfiana (Poltekkes Kemenkes Surakarta, 2024)
Background: Anemia in adolescent girls is a health problem that is still commonly found and has an impact on decreased learning concentration, productivity, and reproductive health. One non-pharmacological alternative that can help increase hemoglobin levels is the consumption of beet juice, which contains iron, folate, and vitamin C. This study aims to determine the effectiveness of beetroot juice in increasing hemoglobin levels in adolescent girls with anemia. Methods: This study used a literature review design by searching articles from the Google Scholar and PubMed databases. The search strategy was conducted using the keywords